2013
DOI: 10.1038/bjc.2013.167
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-associated CD66b+ neutrophil count is an independent prognostic factor for recurrence in localised cervical cancer

Abstract: Background:The prognostic impact of tumour-promoting immune cells in cervical cancer is unclear.Methods:Federation of Gynaecology and Obstetrics (FIGO) stage IB and IIA cervical cancer patients (N=101) were assessed for tumour-associated CD66b+ neutrophils and CD163+ macrophages by immunohistochemistry in whole tissue sections using stereology. Results were correlated with previous results on tumour-infiltrating CD3+, CD4+, and CD8+ lymphocytes in the same cohort with recurrence-free survival (RFS) as end poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 35 publications
6
80
0
Order By: Relevance
“…Selective depletion of neutrophils inhibited tumor angiogenesis and growth in vivo [57]. Also, CXCL5 has been shown to be Recurrent localized cervical cancer Tumor-associated neutrophil count is an independent factor for short recurrence-free survival [139] Epithelial ovarian cancer Pre-operative NLR in ovarian cancer subjects (mean 6.02) was significantly higher than in benign ovarian tumor subjects (mean 2.57) and healthy controls (mean 1.98). Elevated NLR may predict an adverse outcome.…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 98%
See 1 more Smart Citation
“…Selective depletion of neutrophils inhibited tumor angiogenesis and growth in vivo [57]. Also, CXCL5 has been shown to be Recurrent localized cervical cancer Tumor-associated neutrophil count is an independent factor for short recurrence-free survival [139] Epithelial ovarian cancer Pre-operative NLR in ovarian cancer subjects (mean 6.02) was significantly higher than in benign ovarian tumor subjects (mean 2.57) and healthy controls (mean 1.98). Elevated NLR may predict an adverse outcome.…”
Section: Prognostic Values Of Neutrophils and Other Myeloid Subtypes mentioning
confidence: 98%
“…However, neutrophils are also actively recruited into the tumor microenvironment in both cancer patients and mouse models of cancer. In humans, intratumoral infiltration of neutrophils has been detected in gastric carcinoma [200][201][202], bronchioloalveolar carcinoma [170,203], non-small cell lung carcinoma [204], pancreatic neoplasia [205], pancreatic ductal adenocarcinoma [206], bladder cancer [147], glioma [207], cervical carcinoma [139] and breast carcinoma [4,208] ( Table 1). The clinical consequences of intratumoral and circulating neutrophils in cancer patients will be discussed in "Prognostic Values of Neutrophils and Other Myeloid Subtypes in Cancer Patients" section.…”
Section: Neutrophil Recruitment To the Tumor Microenvironmentmentioning
confidence: 99%
“…Therefore, it is not surprising that neutrophils, a key inflammatory cell type, can be mobilized and recruited to tumors. In fact, aberrant accumulation of neutrophils has been documented in a wide variety of tumors and is often associated with poor clinical outcomes (4)(5)(6)(7)(8)(9)(10)(11). Emerging evidence also suggests that neutrophils, in response to signals derived from cancer cells or stromal cells, can alter their phenotypes and migration routes and also release factors that act on tumor cells and other cell types (e.g., endothelial cells and immune cells), which we review in the following sections.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that systemic inflammation and the tumor-associated inflammatory microenvironment serve an important additional role in modulating chemotherapeutic responsiveness and chemoresistance; however, the underlying mechanisms remain largely unclear (8,29). Hematological markers of systemic inflammation, including C-reactive protein, PNC, NLR, PLR, albumin-neutrophil prognostic grade etc., are well established as useful in the prediction of outcomes in a number of cancer types (19)(20)(21)(22)(23)(25)(26)(27)(28)(37)(38)(39)(40). Nevertheless, there is a paucity of studies regarding the associations between inflammatory indexes and chemotherapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, indexes of inflammatory cells [including the pretreatment neutrophil count (PNC), macrophage, neutrophil-lymphocyte ratio (NLR) and platelet-lymphocyte ratio (PLR)] in the bloodstream can reflect the scope and extent of inflammation (18,19). Previous studies have reported that elevations in the PNC, NLR or PLR indicate a poor prognosis in various human cancer types, most notably in colorectal cancer (19), hepatocellular carcinoma (20), and in gastric (21), esophageal (22), breast (23,24), ovarian (25), cervical (26) and lung cancer (27,28). Increasingly, studies have suggested that inflammation serves an important role in the regulation of chemoresistance (8,(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%